Ottoman historical documents : the institutions of an empire - Ménage, Victor Louis, 1920-2015. (Edinburgh, UK)
xxii, 207 sayfa
Keywords: “Translates and comments on Ottoman documents from the period of the empire's rise to greatness. The first systematic collection of source materials for students of Ottoman history. Fluently translates the documents from Ottoman Turkish, Greek, Arabic, Persian, Latin and Italian into English. Explains technical terms and problems of interpretation with annotations and a glossary. Contextualises the documents in a succinct introduction to each chapter. Introduces both the government and institutions of the Ottoman Empire, and the different types of source material encountered in historical research. Provides valuable comparative material for historians of the late-mediaeval and early modern periods, and in particular for historians of the Mediterranean and Middle East during this era. This collection of translated primary sources for Ottoman history shows how the major institutions of Ottoman government developed and functioned” --